A RECORD OF FLUCTUATING BOTTOM CURRENTS ON THE SLOPES WEST OF THE PORCUPINE BANK, OFFSHORE IRELAND - IMPLICATIONS FOR LATE QUATERNARY CLIMATE FORCING - Øvrebø L.K.; Haughton P.D.W.; Shannon P.M. (My University, 2006)
Both local and regional controls on slope sedimentation west of Porcupine Bank are assessed using an array of 25 gravity cores, integrated with shallow seismic, TOBI side-scan and high-resolution bathymetry data. The cores were retrieved from an area of smooth, distally steepened slope (between 52° and 53°N) in water depths of 950 to 2750 m. The slope here is unmodified by gravity failures and is swept by bottom currents that flow from S to N along the margin. The cores reveal a coherent shallow stratigraphy that can be traced along and between transects at upper-, mid- and lower-slope levels. AMS 14C dating, oxygen-isotopes and carbonate profiles suggest the cored record could extend as far back as 500 ka in the longest cores, with most cores providing details of the slope response to the last interglacial, last glacial and Holocene forcing. The facies indicate deposition was dominated by a combination of bottom currents, ice-rafting and hemipelagic settling, with carbonate-prone deposits during interglacials, and siliciclastic deposits during glacials. Inferred contourites imply that strong currents operated during interglacials, with weaker current reworking during glacial conditions. A pair of erosion surfaces record significant mid- and upper-slope scouring during Marine Isotope Stage (MIS 3) and in the Early Holocene. The lateral facies distribution implies stronger currents at shallower levels on the slope, although there is evidence that the core of the current migrated up and down the slope, and that sand might locally have spilt down-slope. The bathymetry influenced both the wider geometry of the condensed contourite sheet and the local thickness and facies variation across the slope. A significant result of the study is the identification of a pair of thin sand-mud contourite couplets that record enhanced bottom-current reworking corresponding to periods of interstadial warming during MIS 3. The couplets can be correlated to the terrestrial records onshore Ireland and imply that the NE Atlantic margin oceanographic and onshore climate records are strongly coupled at interstadial level. © 2005 Elsevier B.V. All rights reserved.
Keywords: BOTTOM CURRENTS; CONTOURITES; GLACIAL CYCLES; PORCUPINE BANK; SLOPE SEDIMENTATION; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен